Reason in Education Review (Study of the Philosophy of Education in the Perspective of the Verses of the Qur'an) - Jauhar Syarifah; A'isyah Rosa Octavia; Lyza Habibah; A. Nurul Kawakib (Edumaspul: Jurnal Pendidikan, 2022)
Human nature is a truth-seeking creature. In seeking the truth, knowledge is needed which requires reason. Reason is a very important tool for humans that differentiates them from other creatures. Both reason and the Qur'an are interconnected in Islamic science because the Qur'an always has brilliant answers to problems that exist on this earth. In line with the development of knowledge, studies related to reason and verses of the Qur'an are needed especially in responding to educational challenges. The results of this research show that: first, reason is the power of thought which if used can lead each individual to understand and solve the problems that are in his mind, second, reason has major implications for the goals of Islamic education which determine the success or failure of educators in achieving the goals of Islamic education.